STRATEGI GURU DALAM MENUMBUHKAN SIKAP PEDULI SOSIAL SISWA KELAS IV MELALUI PEMBELAJARAN IPAS DI SEKOLAH DASAR - Lusy Rahmawati; Zalfa Nabila Aprilianti; Dessy Cahaya Permata; Muhammad Imaduddin; Arif Mahya Fanny (STKIP Subang, 2026)
This study was motivated by the decline of social care attitudes among elementary school students, such as lack of empathy toward peers, low social interaction, and inappropriate behavior in the school environment. The purpose of this study was to determine the teacher’s strategies in fostering social care attitudes among fourth-grade students through Science and Social Studies (IPAS) learning at SDN Purwodadi. This research employed a qualitative method with a descriptive approach. The research subjects consisted of the fourth-grade homeroom teacher and fourth-grade students. Data were collected through observation, interviews, and documentation to obtain in-depth information regarding the strategies implemented by the teacher. The results showed that teachers applied various strategies to develop students’ social care attitudes, including group discussions, collaborative learning, habituation of social values, teacher role modeling, the use of interactive learning media, and collaboration with parents. These strategies were able to improve students’ social interaction, cooperation, empathy toward peers, and participation in social activities at school. Although several obstacles were encountered, such as differences in students’ characteristics and lack of focus during learning, teachers addressed these challenges through individual approaches and by creating an enjoyable learning atmosphere. Therefore, IPAS learning integrated with character education was proven to effectively support the development of social care attitudes among elementary school students.